Molecular Characterization and Expression of OfJNK and Ofp38 in Ostrinia furnacalis (Guenée) Under Different Environmental Stressors - Su, Li; Meng, Jian-Yu; Yang, Hong; Zhang, Chang-Yu (Frontiers in Physiology, 2020)
Ostrinia furnacalis, an important pest of corn, has substantial detrimental effects on corn production. The mitogen-activated protein kinase (MAPK) signaling pathway plays a pivotal role in an insect’s resistance to environmental stress. The expression levels of JNK and p38 have been well-recorded in several insects under different environmental stressors, at different developmental stages, and in various tissue types; however, there is limited information on JNK and p38 in agricultural insects. To clarify the mechanism whereby O. furnacalis responds to environmental stress, we cloned JNK and p38 gene from Ostrinia furnacalis and subsequently named them OfJNK and Ofp38, respectively. Further, we examined the expression levels of OfJNK and Ofp38 under different environmental stressors. In this study, we obtained full-length sequences of OfJNK and Ofp38, and RT-qPCR results showed that these genes were expressed at all developmental stages, in various tissues (head, chest, abdomen, leg, wing, antennae, compound eye, midgut, and ovary) and under different environmental stressors (4°C and ultraviolet A treatment for 0, 30, 60, 90, and 120 min). The expression levels of OfJNK and Ofp38 were relatively higher in eggs and 3-day-old adult females than in other developmental stages. Moreover, the expression level of OfJNK was higher in the wings than in other tissues, whereas that of Ofp38 was significantly higher in the ovaries than in other tissues. OfJNK and Ofp38 showed high expression 90 min after being subjected to treatment at 4°C and ultraviolet A irradiation; the expression of Ofp38 peaked at 30 min, whereas that of OfJNK peaked at 60 min. These results indicate that O. furnacalis differs in terms of its response under different environmental stressors. In summary, our results will provide a foundation for additional research needed to determine the role of the MAPK signaling pathway and the underlying mechanisms by which it shows resistance to environmental stresses in insects.